2003
DOI: 10.2105/ajph.93.6.994
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Cognitive Decline in Midlife: Evidence From a Prospective Birth Cohort Study

Abstract: The present results show that heavy smoking is associated with cognitive impairment and decline in midlife. Smokers who survive into later life may be at risk of clinically significant cognitive declines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
139
3
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(165 citation statements)
references
References 18 publications
9
139
3
8
Order By: Relevance
“…A growing body of evidence suggests that chronic smoking, independent of substance abuse disorders, is associated with adverse effects on several domains of neurocognition, including executive skills, learning and memory, processing speed, and working memory (e.g., Ernst et al, 2001;Heffernan et al, 2005;Kalmijn et al, 2002;Paul et al, 2006;Razani et al, 2004;Richards et al, 2003). In a large cohort of community-recruited actively drinking and abstinent alcoholics, Glass et al (2006) found that both alcoholism and smoking severity were inversely related to neurocognitive function, and smoking severity (i.e., pack years) was a unique predictor of general intelligence and cognitive proficiency (i.e., an index of both speed and accuracy).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that chronic smoking, independent of substance abuse disorders, is associated with adverse effects on several domains of neurocognition, including executive skills, learning and memory, processing speed, and working memory (e.g., Ernst et al, 2001;Heffernan et al, 2005;Kalmijn et al, 2002;Paul et al, 2006;Razani et al, 2004;Richards et al, 2003). In a large cohort of community-recruited actively drinking and abstinent alcoholics, Glass et al (2006) found that both alcoholism and smoking severity were inversely related to neurocognitive function, and smoking severity (i.e., pack years) was a unique predictor of general intelligence and cognitive proficiency (i.e., an index of both speed and accuracy).…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be interpreted as evidence for a deleterious effect of cigarette smoking. In support of this interpretation, a study of a large cohort found that smokers exhibited greater decline in performance between the ages of 43 and 53 on a word learning task, as compared to non-smokers (Richards, Jarvis, Thompson, & Wadsworth, 2003). Other studies, however, have not demonstrated significant associations between chronic smoking and cognitive decline (Carmelli, Swan, LaRue, & Eslinger, 1997;Schinka et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…While nicotine may acutely facilitate learning and memory (Levin and Simon, 1998;Newhouse et al, 2004;Sacco et al, 2004), a growing body of evidence suggests chronic cigarette smoking in non-alcoholic individuals adversely affects multiple domains of neurocognition (e.g., Deary et al, 2003;Razani et al, 2004), including learning and memory (Heffernan et al, 2005;Hill et al, 2003;Richards et al, 2003;Schinka et al, 2003). Chronic cigarette smoking, in addition to alcohol, results in additional oxidative stress to brain cells (Moriarty et al, 2003), and cigarette smoke contains many toxic compounds (Fowles et al, 2000) that may directly or indirectly compromise central nervous system tissue , possibly leading to volumetric and/or metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%